Penyuluhan Islamic Parenting untuk Membangun Karakter Anak Saleh di SDN Pakel Yogyakarta - Hidayatullah, Hidayatullah; Muryanto, Muryanto (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This community service activity focuses on counseling Islamic parenting for parents of students at SDN Pakel Yogyakarta. The program aims to introduce Islamic values as a fundamental method for raising children to become pious individuals, aligning with government recommendations to address the rising cases of juvenile delinquency. Using the Service Learning method, the activity integrates observation, socialization, lectures, and evaluation, fostering active engagement between participants and facilitators. Conducted in the SDN Pakel hall, this initiative involved a structured approach to delivering materials and engaging parents in discussions and practical sessions on Islamic parenting practices inspired by the teachings of Prophet Muhammad (PBUH). The results revealed a significant increase in parents' motivation and enthusiasm to apply Islamic parenting principles. Furthermore, the program successfully provided parents with fresh perspectives and a deeper understanding of the importance of incorporating Islamic values in their parenting approach, many of which were previously unfamiliar to them.